THE EFFECT OF COUNTRIES’S CULTURE IN FAMILY FIRMS’ EARNINGS QUALITY: AN EXAMINATION ALIGNMENT VERSUS ENTRENCHMENT APPROACH IN AGENCY THEORY - Basuki, Hardo; Nurim, Yavida; Anggraini, Francisca Reni Retno (Unand Press, 2015)
The studies of the family firms’ earnings quality have not yet concluded about individual or family as majority owner in firm has positive or negative influence over the earnings quality. We conjecture that the prior researches use the different approaches: such as alignment versus entrenchment, to explain agency conflict between majority and minority shareholders. Prior researches have proved that culture has relation with accounting practice in a country. We argue that culture also stimulates the individual or family’s behaviour in that firm to choose the alignment or entrenchment behaviour. This study examines the accruals (discretionary accruals, discretionary current accruals, and discretionary long-term accruals) level, as the proxy of earnings quality, of the family firms in four culture dimensions which established by Hofstede’s (1997). This study uses three groups of shareholders in family firms as samples (the one largest, the two largest, and the three largest shareholders) from 48 countries around the world. Based on ANOVA, this study proved that the difference of culture level has the different earnings quality. The result also reveals that there are different accruals pattern in different culture, such as power distance and individualism (collectivism) have linear pattern, but femininity (masculinity) and uncertainty avoidance have non-linear pattern. The linear accruals pattern implies that large (small) power distance or individualism (collectivism) culture has low (high) earnings quality or high (low) earnings quality, respectively. However, for the non linear accruals pattern of femininity (masculinity) or uncertainty avoidance culture implies that the evidence do not conform the prior research that masculinity has positive correlation with corruption level in societies or strong uncertainty avoidance concerns to more precise law.